Analisis Semiotika Logo UIN Sumatera Utara: Pendekatan Tanda dan Makna Menurut Teori Charles Sanders Peirce - Liana Hutapea; Siti Auliza Fatma Nasution; Muhammad Fikri Alif Ghani; Nursiah Nursiah; Hanif Maulana Pratama; Riki Novianto; Amanda Yasmintia; Mauly Efendi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to analyze the logo of the State Islamic University of North Sumatra (UINSU) using Charles Sanders Peirce's semiotic approach. Peirce's theory divides signs into icons, indexes, and symbols, and views meaning through a triadic process: representamen, object, and interpretant. With a qualitative approach, this study identifies visual elements in the UINSU logo and interprets their meaning based on the context of Islam, science, and nationalism. The results of the analysis show that each visual component, whether shape, color, or typography, contains deep philosophical and ideological meanings and represents the identity and institutional vision of UINSU.